2007
DOI: 10.1142/s0192415x07004990
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Dauricine on Inflammatory Process Following Focal Cerebral Ischemia/Reperfusion in Rats

Abstract: Our previous experimental studies showed that dauricine could protect the brain from ischemic damage, but the underlying mechanisms were unknown. In this study, we investigated the effect of dauricine on the changes of the inflammation process induced by ischemia/reperfusion (I/R). After I/R, the enzyme activity of MPO, the expression of ICAM-1 and the transcription of IL-1beta and TNF-alpha mRNA were all significantly increased (p < 0.01). And after treatment with dauricine, they were all significantly reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 17 publications
1
42
0
Order By: Relevance
“…Dauricine (Dau; Figure 1), a bisbenzylisoquinoline alkaloid isolated from the rhizome of Menispermum dauricum DC, has been found to have antiarrhythmic and antiinflammatory effects [1] . Recently, several studies have demonstrated that Dau has potent anticancer activities, including inhibition of growth [2] , reduction of drug resistance, and promotion of apoptosis in various tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Dauricine (Dau; Figure 1), a bisbenzylisoquinoline alkaloid isolated from the rhizome of Menispermum dauricum DC, has been found to have antiarrhythmic and antiinflammatory effects [1] . Recently, several studies have demonstrated that Dau has potent anticancer activities, including inhibition of growth [2] , reduction of drug resistance, and promotion of apoptosis in various tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although we find little literature about the effects of Dc on ischemia/reperfused rat kidneys, YEH et al had reported that Dc has protective effects against apoptosis in mouse testes (30). It is well known that I/R injury increases the interleukin 1-beta (IL-1β) levels in several tissues (13,29). It has been reported that Dc can suppress the expression of IL-1β on cultured conjunctival epithelial cells (28) and that Dc inhibits the matrix metalloproteinases (MMPs) suggesting that it has inhibitory effects on various MMPs (8).…”
mentioning
confidence: 99%
“…Transient focal ischemia was made by intraluminal middle cerebral artery (MCA) blockade with a 3-0 nylon suture, as described previously (Yang et al, 2007). The animals were kept on an isothermal pad.…”
Section: Transient Focal Cerebral Ischemiamentioning
confidence: 99%
“…Previous studies in our laboratory and others have observed that it reduces energy depletion and oxidative stress (Li and Gong, 2004;He et al, 1997). Recently, we demonstrated that multiple pre-ischemic doses of dauricine reduced infract size Yang et al, 2005) by inhibiting the release of cytochrome c and the activation of caspase 9 and caspase 3 (Li et al, 2007a). Furthermore, dauricine suppressed the decrease of mitochondrial membrane potential ( ψ m ) induced by hypoxia and hypoglycaemia (Li et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%